A critical evaluation of the approaches to targeted protein degradation for drug discovery. (April 2019) - Chopra, Rajesh; Sadok, Amine; Collins, Ian
Abstract : There is a great deal of excitement around the concept of targeting proteins for degradation as an alternative to conventional inhibitory small molecules and antibodies. Protein degradation can be undertaken by bifunctional molecules that bind the target for ubiquitin mediated degradation by complexing them with Cereblon (CRBN), von Hippel-Lindau or other E-3 ligases. Alternatively, E-3 ligase receptors such as CRBN or DCAF15 can also be used as a 'template' to bind IMiD or sulphonamide like compounds to degrade multiple context specific proteins by the selected E-3 ligases. The 'template approach' results in the degradation of neo-substrates, some of which would be difficult to drug using conventional approaches. The chemical properties necessary for drug discovery, the rules by which neo-substrates are selected by E-3 ligase receptors and defining the optimal components of the ubiquitin proteasome for protein degradation are still to be fully elucidate. Theis review will aim to critically evaluate the different approaches and principles emerging for targted protein degradation.